DETERMINANTS OF BURNOUT SYNDROME AMONG NURSES AT DELIA GENERAL HOSPITAL, LANGKAT - Sembiring, Esra F.; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (HEARTY, 2026)
Burnout syndrome is characterized by gradual physical and mental exhaustion, marked by cynicism, emotional detachment, negative attitudes toward work, and decreased professional performance due to prolonged job-related stress. Nurses are among the most vulnerable healthcare professionals to burnout, which can adversely affect both service quality and their personal health. This study aimed to analyze the influence of internal and external factors on burnout syndrome among nurses at Delia General Hospital, Langkat. This study employed a quantitative analytic correlation design with a cross-sectional approach. The research was conducted at Delia General Hospital, Langkat. The population consisted of all nurses working at the hospital, totaling 86 respondents. Data were analyzed using the chi-square test and multiple logistic regression. The results showed that coworker support (p = 0.040) and family support had a significant influence on burnout syndrome among nurses at Delia General Hospital, Langkat. In contrast, age, gender, years of service, and supervisor support were not significantly associated with burnout syndrome. This study highlights the importance of strengthening social support in the workplace and developing effective stress management strategies to prevent burnout among nurses. The findings are expected to serve as a reference for hospital management in designing occupational health protection programs and improving the well-being of nursing staff.